Group B Streptococcus pilus sortase regulation: a single mutation in the lid region induces pilin protein polymerization in vitro. Issue 8 (30th April 2013) - Cozzi, Roberta; Zerbini, Francesca; Assfalg, Michael; D'Onofrio, Mariapina; Biagini, Massimiliano; Martinelli, Manuele; Nuccitelli, Annalisa; Norais, Nathalie; Telford, John L.; Maione, Domenico; Rinaudo, C. Daniela
Abstract : Gram‐positive bacteria build pili on their cell surface via a class C sortase‐catalyzed transpeptidation mechanism from pilin protein substrates. Despite the availability of several crystal structures, pilus‐related C sortases remain poorly characterized to date, and their mechanisms of transpeptidation and regulation need to be further investigated. The available 3‐dimensional structures of these enzymes reveal a typical sortase fold, except for the presence of a unique feature represented by an N‐terminal highly flexible loop known as the "lid." This region interacts with the residues composing the catalytic triad and covers the active site, thus maintaining the enzyme in an autoinhibited state and preventing the accessibility to the substrate. It is believed that enzyme activation may occur only after lid displacement from the catalytic domain. In this work, we provide the first direct evidence of the regulatory role of the lid, demonstrating that it is possible to obtain in vitro an efficient polymerization of pilin subunits using an active C sortase lid mutant carrying a single residue mutation in the lid region. Moreover, biochemical analyses of this recombinant mutant reveal that the lid confers thermodynamic and proteolytic stability to the enzyme.—Cozzi, R., Zerbini, F., Assfalg, M., D'Onofrio, M., Biagini, M., Martinelli, M., Nuccitelli, A., Norais, N., Telford, J. L., Maione, D.Rinaudo, C. D., Group B Streptococcus pilus sortase regulation: a single mutation in the lid region induces pilin protein polymerization in vitro . FASEB J. 27, 3144–3154 (2013). www.fasebj.org